Bermatematika, Berkarakter - Syafri Ahmad (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
To shape the personality of students in civilized and humane education, the role of the school is very important. In the process of learning in the classroom in particular, educators should think about what strategies will be used in dealing with learners when learning takes place. Learning strategies can make learning more conducive and not monotonous. Thus making the students more interested in following further subject matter that will be given by educators. Until now, there has been no application that focuses more on cultural values ​​and the character of the teaching of mathematics in elementary school. More in-depth character education in mathematics.Though cultural values ​​and character need to be instilled in the students as early as possible. Elementary school is the most appropriate body as a container application character education, character education has diperkenalakan although implicitly at home. Then, another virtue of this research is as an input for melaksananakan teachers in the learning process in order to foster a culture and character of learners who baik.Kegiatan this study aims to develop a mathematical model of learning through Character Education using PMRI approach in primary schools. The development of a model that is expected to be used in a practical, valid and effective, so that the learning objectives set out in the curriculum of mathematics can be achieved by optimal as possible.